LH StegTool for company Lian Heng Management - YU, JIA JUN; RAHIM, NORDIANA (Applied Information Technology And Computer Science, 2023)
LH StegTool is an image steganography tool that allows Lian Heng (LH) Management two in-charge employees to conceal sensitive information within images. Steganography is a technique used to concealing information with various medium such as images, videos, audio, text and protocol, in order to prevent information from being disclosed to a third party. LH StegTool was created using steganography and cryptography; Cryptography was used to encrypt the hidden data by using Advanced Encryption Standard algorithm, encrypt the image by using Data Encryption Standard and steganography with the Least Significant Bit algorithm was used to embed the encrypted hidden data into the image. After the process of embedded message, an image with the hidden data is generated, which is known as a stego-image. The Object-Oriented Software Development Model is used to develop LH StegTool. This paper offered an overview of steganography and proved that LH StegTool can successfully handle the problem that the target company was experiencing, as well as secure the sensitive information of the company and their customers.